(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Ankle brachial index test is used as a guide in maxillofacial surgery to detect any abnormalities associated with circulation in the lower extremities. This index is about 1 or 1.1 in normal conditions, if it is decreased or increased this mean that there are some abnormalities in haemodynamic such as peripheral arterial diseases. A study carried out in Al-Hilla surgical hospital including 20 patients for estimation of ankle-brachial index(volunteers) to show their fitness for free flap surgery. The results were normal in 13 patients, most of them in young adult groups